The Influence of Social Media-Based Nutrition Education on Adolescents' Nutritional Knowledge and Body Image Perception - Ansar, Ansar; Hartini, Diah Ayu; Bahja, Bahja; Faisal, Elvyrah; Dewi, Nikmah Utami; Aiman, Ummu (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Adolescents are a group vulnerable to nutritional problems due to their ongoing growth phase. A lack of nutritional knowledge and poor body image perception can negatively impact their nutritional status. Nutrition education is essential to enhance adolescents' knowledge, shaping healthy attitudes and behaviors regarding diet and other factors influencing food choices. This study utilized WhatsApp as an educational media platform. This study aimed to analyze the effect of social media-based nutrition education on adolescents' nutritional knowledge and body image perceptions. This descriptive research employed a quasi-experimental approach with a one-group pre-test and post-test design. The study was conducted in high schools in Palu City, Central Sulawesi, from January to June 2024. Data collected included respondent characteristics, knowledge levels, and body image perceptions. Data collection involved administering a nutrition knowledge questionnaire and assessing body image perception using the Figure Rating Scale (FRS). The data were analyzed using a paired sample t-test. The results revealed a significant effect of social media-based nutrition education on both adolescents' nutritional knowledge and body image perceptions, with a significance value of ????<0.05. There was a 61% increase in the percentage of adolescents with sufficient knowledge. Additionally, there was a 25% increase in the number of adolescents satisfied with their body shape.